2017
DOI: 10.3892/etm.2017.4747
|View full text |Cite
|
Sign up to set email alerts
|

Perfusion-weighted magnetic resonance imaging in the assessment of haemodynamics following stent angioplasty in patients with symptomatic middle cerebral artery plaque stenosis at the M1 segment

Abstract: The most effective strategy to assess changes in the brain haemodynamics of stent angioplasty in patients with symptomatic ischemia of the M1 segment of the middle cerebral artery (MCA) remains unknown. The purpose of the present study was to use perfusion-weighted magnetic resonance imaging (PWI) to evaluate the effect of stent angioplasty in treating patients with symptomatic MCA plaque stenosis. Stent angioplasty was performed on 23 patients with reduplicative transient ischaemic attack who were refractory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 24 publications
2
5
1
Order By: Relevance
“…However, the sample size (n = 28) of the previous study (31) is smaller than our study and unusable for association analysis. Affected cerebral blood flow was observed in patients with severe steno-occlusive MCA (12,26), and there is evidence that reduced cerebral blood flow is a factor in CSVD (32). Contrastly, cerebral blood flow was not significantly affected in patients with moderate MCA stenosis (26), which might account for the negative association between moderate MCA stenosis and BG-EPVS in our study.…”
Section: Discussioncontrasting
confidence: 50%
See 3 more Smart Citations
“…However, the sample size (n = 28) of the previous study (31) is smaller than our study and unusable for association analysis. Affected cerebral blood flow was observed in patients with severe steno-occlusive MCA (12,26), and there is evidence that reduced cerebral blood flow is a factor in CSVD (32). Contrastly, cerebral blood flow was not significantly affected in patients with moderate MCA stenosis (26), which might account for the negative association between moderate MCA stenosis and BG-EPVS in our study.…”
Section: Discussioncontrasting
confidence: 50%
“…Moreover, previous experimental studies showed hypoperfusion secondary to internal carotid artery ligation (33) or MCA occlusion (34) caused impaired CSF influx. Based on these findings, we propose that hypoperfusion caused by severe-occlusive MCA could trigger hypoxia (12,14,35), impair the interstitial fluid drainage system (1,3), and in turn facilitate the formation of BG-EPVS (1,8). This hypothesis needs to be tested in longitudinal studies.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Perfusion imaging has also been used to assess collateral circulation and indirectly qualify clinical outcome ( 4 ). Transient ischemic attack and internal carotid artery blockage and stenosis are also identifiable with perfusion imaging ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%